2022
DOI: 10.1155/2022/1691382
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation into Parental Perceptions Surrounding the Impact of Mobile Media Use on Child Behavior and Executive Functioning

Abstract: Children demonstrate increasing early engagement with mobile media facilitated by its portability and interactivity. Parents are known to employ a range of mediation strategies for mobile media use but continue to have limited awareness about the impact of mobile media on their child’s executive functioning. Mobile media use has previously been shown to be negatively correlated with the executive functioning development of a child; however, little is known of how parents approach their child’s mobile media use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…They may be using these rules to keep the various gadgets under their control but may not be aware of the harmful effects it causes or the proper ways to control screen time. A study by Milford et al, 34 reported that the majority of parents use both restrictive and active mediation methods to limit screen use which sometimes resulted in tension and opposition from children leading to increased screen time. Another study by Samaha et al 35 found that screen media rules by parents are negatively associated with exceeding the limit for screen time.…”
Section: Discussionmentioning
confidence: 99%
“…They may be using these rules to keep the various gadgets under their control but may not be aware of the harmful effects it causes or the proper ways to control screen time. A study by Milford et al, 34 reported that the majority of parents use both restrictive and active mediation methods to limit screen use which sometimes resulted in tension and opposition from children leading to increased screen time. Another study by Samaha et al 35 found that screen media rules by parents are negatively associated with exceeding the limit for screen time.…”
Section: Discussionmentioning
confidence: 99%
“…It also uses an inclusive term "screen media" to screen the children's problematic use of many devices such as video games, mobile phones, tablets, and other devices rather than screening the problematic use of specific device. This is particularly advantageous since children are currently using diverse media platforms [1,15].…”
Section: Discussionmentioning
confidence: 99%
“…Also, research revealed that parenting practices regarding screen media use restriction were associated with less screen time among children [28]. However, parents usually fail in enforcing rules and restrictions that control their children's use of media [1]. Supporting the parents' beliefs about problematic use of media through using this simple tool might increase their self-efficacy in enforcing screen media restriction rules [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the soaring number of Internet users, Shek and Yu [1] warned that Internet addiction is a raising issue over the world, especially in adolescents. Milford et al [2] observed that students grow accustomed to using various types of social media (e.g., blogs, social networks, and forums) for different purposes, such as entertainment, learning, and communication. However, spending a lot of time on the Internet can be detrimental to education, work, and relationships [3].…”
Section: Introductionmentioning
confidence: 99%